Rethink of EGFR in Cancer With Its Kinase Independent Function on Board - Thomas, Rintu; Weihua, Zhang (Frontiers in Oncology, 2019)
The epidermal growth factor receptor (EGFR) is one of most potent oncogenes that are commonly altered in cancers. As a receptor tyrosine kinase, EGFR’s kinase activity has been serving as the primary target for developing cancer therapeutics, namely the EGFR inhibitors including small molecules targeting its ATP binding pocket and monoclonal antibodies targeting its ligand binding domains. EGFR inhibitors have produced impressive therapeutic benefits to responsive types of cancers. However, acquired and innate resistances have precluded current anti-EGFR agents from offering sustainable benefits to initially responsive cancers and benefits to EGFR-positive cancers that are innately resistant. Recent years have witnessed a realization that EGFR possesses kinase-independent (KID) pro-survival functions in cancer cells. This new knowledge has offered a different angle of understanding of EGFR in cancer and opened a new avenue of targeting EGFR for cancer therapy. There are already many excellent reviews on the role of EGFR with a focus on its kinase-dependent functions and mechanisms of resistance to EGFR targeted therapies. The present opinion aims to initiate a fresh discussion about the function of EGFR in cancer cells by laying out some unanswered questions pertaining to EGFR in cancer cells, by rethinking the unmet therapeutic challenges from a view of EGFR’s KID function, and by proposing novel approaches to target the KID functions of EGFR for cancer treatment.